Functional Niche Competition Between Normal Hematopoietic Stem and Progenitor Cells and Myeloid Leukemia Cells. (5th October 2015) - Glait-Santar, Chen; Desmond, Ronan; Feng, Xingmin; Bat, Taha; Chen, Jichun; Heuston, Elisabeth; Mizukawa, Benjamin; Mulloy, James C.; Bodine, David M.; Larochelle, Andre; Dunbar, Cynthia E.
Abstract : Hematopoietic stem and progenitor cells (HSPCs) reside in a specialized niche that regulates their proliferative capacity and their fate. There is increasing evidence for similar roles of marrow niches on controlling the behavior of leukemic cells; however, whether normal hematopoietic stem cell (HSC) and leukemic cells reside in or functionally compete for the same marrow niche is unclear. We used the mixed lineage leukemia-AF9 (MLL-AF9) murine acute myeloid leukemia (AML) in a competitive repopulation model to investigate whether normal HSPC and leukemic cells functionally compete for the same marrow niches. Irradiated recipient mice were transplanted with fixed numbers of MLL-AF9 cells mixed with increasing doses of normal syngeneic whole bone marrow (WBM) or with purified HSPC (LSK). Survival was significantly increased and leukemic progression was delayed proportional to increasing doses of normal WBM or normal LSK cells in multiple independent experiments, with all doses of WBM or LSK cells studied above the threshold for rapid and complete hematopoietic reconstitution in the absence of leukemia. Confocal microscopy demonstrated nests of either leukemic cells or normal hematopoietic cells but not both in the marrow adjacent to endosteum. Early following transplantation, leukemic cells from animals receiving lower LSK doses were cycling more actively than in those receiving higher doses. These results suggest that normal HSPC and AML cells compete for the same functional niche. Manipulation of the niche could impact on response to antileukemic therapies, and the numbers of normal HSPC could impact on leukemia outcome, informing approaches to cell dose in the context of stem cell transplantation. Stem Cells   2015;33:3635–3642